Sintesa Coating Kobalt Oksida Dengan Proses Sol-Gel Dip-Coating Sebagai Solar Selective Absorber : Pengaruh Konsentrasi Molar Co Dan Ulang Deposisi - Dimas Nofriyan; Amun Amri; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The Study of the solar absorber with cobalt oxide as the heat absorbing surfaces has been conducted. A dip-coating technique has been used to deposit cobalt oxide coatings on aluminum substrates. A solution of cobalt oxide was prepared in a bath by first mixing Co(NO3)2.6H2O, ethanol and a small amount of propionic acid. The sol prekursor was stirred for 2 hours at room temperature. Pieces of aluminum with size 2x4x0.5cm were cleaned using a solution of phosphoric acid 10% at temperature 50oC for 10 minutes. The coating was synthesized by varying molar percursors 0.1M; 0.2M; 0.3M and the number of dipping-drying cycles 2x, 4x, 6x, 8x and 10x, then annealed at temperature 550 oC for 1 hour. The solar absorptance and emittance were parameters to characterize the performance of the absorber. In practical terms, this generally corresponded to absorbing short wavelengths up to a certain cut-off wavelength (solar spectrum, UV-VIS-NIR), and a low thermal emittance in the IR wavelength region. Consequently, this research attained high performance solar selective absorber of which solar absorptance was 80,14% and emittance was 7,65% on 4 cylcles. Values of selectivity, α/ɛ = 10,48 were obtained. XRD test showed the crystal structure of cobalt oxide, SEM test showed the surface structure of the coating was relatively homogenous and adhesion test showed the adhesion between the coating and the substrate can be categorized as very strong (5B scale ASTM D 3359).Keyword : coating, solar selective absorber, sol-gel dip-coating